The Role of Phonetic Performance in Grammar - Hassan Ali, Assist. Lect . Maysaa; Ali Yaseen, Prof. Dr. Azhar (Basra studies journal, 2025)
Phonetic performance plays a crucial role in grammar, as its influence is deeply intertwined with the essence of language, which is fundamentally composed of spoken sounds. This research highlights the significant impact of phonetic elements on grammar, with pausing emerging as one of the most influential yet underappreciated aspects. Grammarians have often overlooked the importance of pausing in their studies, whereas reciters have recognized its strong connection to grammar. They have demonstrated that the relationship between pausing and grammar is reciprocal, requiring readers to follow grammatical rules to accurately apply pauses and achieve their intended effect.